Harnessing Technology to Drive Smarter Financial Decision Making - Lalu Rizal Ihwandi; Fredrick Onyango Aila; Rian Destiningsih (Takaza Innovatix Labs Ltd., 2025)
This study investigates the impact of technological adoption—specifically artificial intelligence (AI), big data utilization, and FinTech platform usage—on optimal financial decision-making, with financial literacy positioned as a mediating variable. Using a quantitative research design and data collected from financially active individuals, the model was analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that big data utilization exerts both direct and indirect positive effects on financial decision-making through enhanced financial literacy. While AI and FinTech do not demonstrate significant direct impacts on financial literacy, their indirect effects through literacy pathways are supported. Furthermore, financial literacy is confirmed to play a vital role in mediating the relationship between technology and decision-making outcomes. These findings underscore the need to integrate financial education with technological advancements to ensure users can effectively leverage smart finance tools. The research contributes to the growing body of literature on digital financial behavior and offers actionable insights for developers, educators, and policymakers aiming to foster financially competent users in an increasingly digitized economy.